Paleometry: a brand new area in brazilian science - Delgado, Adriana de Oliveira; Buck, Pedro Victor; Oses, Gabriel Ladeira; Ghilardi, Renato Pirani [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Alves Forancelli Pacheco, Mirian Liza (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
Paleometry is a promising research field that brings together different areas, such as physics and chemistry, applied to paleobiological issues. In spite of being recognized abroad, it is a new research field in Brazil. The most important characteristic is the application of mostly non-destructive techniques to the study of fossils. This work compiles some paleometrical applications to different geological contexts, such as the synthesis of hard skeleton in Corumbella werneri, geochemical aspects about fresh water bivalves from the Bauru Group and the exceptional preservation of arthropods from the Crato Member. Diffuse Reflectance Infrared (DRIFT) and Energy Dispersive X-ray Spectroscopy (EDX) were complementary to elucidate the types of skeletogenesys in Corumbella. In the case of the bivalves, DRIFT revealed to be important to elucidate aspects about death and fossilization. Among arthropods, morphological analysis with Scanning Electron Microscopy (SEM) associated with EDX was more profitable to understand fossilization process and paleoenvironmental implications.
Keywords: Paleometry; FTIR; SEM; EDX; Calcite; Fossilization